Analisis Penerapan Metode HIRARC Untuk Meningkatkan Keselamatan Dan Kesehatan Kerja Pada Konstruksi Saluran Kabel Tegangan Menengah (SKTM) - Muhammad Fathin Taqiyuddin; Syadzadhiya Qothrunada Zakiyayasin Nisa (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Electricity is a vital aspect of modern infrastructure that supports various human activities. Therefore, the increasing need for electrical energy requires good planning to ensure the availability of electrical energy in the future. The transmission system, especially the Medium Voltage Cable Line (MVCL), plays an important role in distributing electrical energy from generators to consumers. However, MVCL construction involves high-risk work, so it requires special attention to occupational health and safety (OHS). This research uses the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method to identify and control risks in MVCL construction projects. It is hoped that the results of this research can provide recommendations for improving occupational safety and health as well as efficiency in future MVCL construction projects.